2013
DOI: 10.1111/1462-2920.12282
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed mutagenesis of the P225, N230 and H272 residues of succinate dehydrogenase subunit B from Botrytis cinerea highlights different roles in enzyme activity and inhibitor binding

Abstract: Carboxamide fungicides target succinate dehydrogenase (SDH). Recent field monitoring studies have identified Botrytis cinerea isolates resistant to one or several SDH inhibitors (SDHIs) with amino acid substitutions in the SDH B subunit. We confirmed, by site-directed mutagenesis of the sdhB gene, that each of the mutations identified in field strains conferred resistance to boscalid in B.cinerea, and in some cases cross-resistance to other SDHIs (fluopyram, carboxin). Enzyme inhibition studies showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 41 publications
4
89
0
3
Order By: Relevance
“…Different single-point mutations in sdh gene are involved in resistance mechanisms of B. cinerea for these compounds (Veloukas et al, 2011(Veloukas et al, , 2013Yin et al, 2011;Veloukas & Karaoglanidis, 2012;Amiri et al, 2014). Our data are in agreement with recent reports (Veloukas et al, 2013;Amiri et al, 2014) as boscalid-resistant isolates used in this study possessed H272R mutation in the SdhB subunit that display a differential sensitivity to the SDHIs (Lalève et al, 2013;De Miccolis Angelini et al, 2014a). Control efficacy of SDHI fungicides confirmed data obtained in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…Different single-point mutations in sdh gene are involved in resistance mechanisms of B. cinerea for these compounds (Veloukas et al, 2011(Veloukas et al, , 2013Yin et al, 2011;Veloukas & Karaoglanidis, 2012;Amiri et al, 2014). Our data are in agreement with recent reports (Veloukas et al, 2013;Amiri et al, 2014) as boscalid-resistant isolates used in this study possessed H272R mutation in the SdhB subunit that display a differential sensitivity to the SDHIs (Lalève et al, 2013;De Miccolis Angelini et al, 2014a). Control efficacy of SDHI fungicides confirmed data obtained in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…There was a high diversity of combinations of resistance mutations in German MR isolates, akin to the situation in the United States (Fernández-Ortuño et al, 2015). These and similar fungicide resistance mutations have sometimes been reported to impair the fitness of Botrytis isolates in the case of fenhexamid (Billard et al, 2012), boscalid (Lalève et al, 2013; Veloukas et al, 2014) and iprodione (Leroux et al, 2002) whereas in other studies no fitness reductions were found (Bardas et al, 2008; Fernández-Ortuño et al, 2013; Amiri et al, 2014; Veloukas et al, 2014). The availability of strains with simultaneous resistance to most or all of these fungicides provided the opportunity to analyse their combined effects on fitness by performing phenotypic comparisons of MR and sensitive field strains.…”
Section: Discussionmentioning
confidence: 82%
“…found a lack of cross‐resistance to fluopyram in very highly and highly boscalid‐resistant isolates of Corynespora cassiicola carrying H278Y and H278R variations in sdhB , respectively, as well as highly boscalid‐resistant isolates of Podosphaera xanthii (Castaggne) U. Braun & N. Shishkoff carrying the H → Y (homologous to H272Y in B. cinerea ) mutation in sdhB . Similarly, fluopyram and isofetamid controlled boscalid‐resistant isolates of B. cinerea that carried H272R/Y mutations in the sdhB gene . As indicated by Scalliet et al ., fluopyram does not have a hydrogen bond acceptor in its molecule, and thus its binding seems to be unaffected by the histidine to tyrosine substitution in the SDHB subunit.…”
Section: Discussionmentioning
confidence: 99%